2009
DOI: 10.1128/aem.01689-08
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Assessment of Salmonella enterica Serovar Enteritidis Inactivated-Vaccine Treatment in Layer Flocks

Abstract: Although there have been several reports on the efficacy assessment of a Salmonella enterica serovar Enteritidis vaccine against intestinal and parenchymatous organ diseases of laying hens, no public health risk characterization of its long-term effect on eggs has been reported. In this study, we attempted to assess the public health effect of an inactivated S. enterica serovar Enteritidis vaccine against serovar Enteritidis contamination of chicken eggs. We analyzed serovar Enteritidis isolation test results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Control strategies could include the use of Salmonellafree parent flocks and Salmonella-free chicken feeds, regular cleaning and disinfection of poultry houses, with empty resting periods between flocks, measures to prevent domestic and wild animals, including wild birds, from gaining access to the premises, vaccination of breeder and layer flocks [19,20], and intensive flock-level testing with destruction of infected flocks [21]. However, apparently expensive measures could eventually be cost-effective as reduction of Salmonella in food animals would most likely lower the burden of human infections and reduce the cost associated with such illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Control strategies could include the use of Salmonellafree parent flocks and Salmonella-free chicken feeds, regular cleaning and disinfection of poultry houses, with empty resting periods between flocks, measures to prevent domestic and wild animals, including wild birds, from gaining access to the premises, vaccination of breeder and layer flocks [19,20], and intensive flock-level testing with destruction of infected flocks [21]. However, apparently expensive measures could eventually be cost-effective as reduction of Salmonella in food animals would most likely lower the burden of human infections and reduce the cost associated with such illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination works by reducing the prevalence of Salmonella in breeder hens and their progeny (19,23,25) or by increasing the passive immunity of meat birds and blocking the horizontal transmission of Salmonella to broiler chickens (22,25,35). However, there have been few studies focusing on whether the vaccines are effective in reducing Salmonella on a commercial scale (13,14,16,17,34,39).…”
mentioning
confidence: 99%
“…Hygiene and biosecurity in addition to the administration of an appropriate form of oil emulsion bacterium against S. Enteritidis in flocks of farms A, B, C and D could be some of the factors that contributed to the absence of this serovar. In a study conducted in Japan, S. Enteritidis was isolated in several samples of faeces, eggs and the environment from farms containing vaccinated and unvaccinated flocks and the percentage of isolation was lower in flocks where the oil-emulsion bacterin against S. Enteritidis was administered (Toyota-Hanatani et al, 2009). Freitas Neto et al (2008) also reported reductions in shedding of S. Enteritidis and egg contamination in laying hens experimentally vaccinated with bacterin.…”
Section: Flocks Of Adult Laying Hens From Farms Serovarsmentioning
confidence: 94%